(untitled) (ACTA DIURNA KOMUNIKASI, 2016)
40 years recently, the population of â€œyaki hitamâ€ or black crested macaque (Macaca nigra) has constantly decrease until 80 % which means only around 5000 cresteds are alive surrounded the primery jungle in North Sulawesi province. It is cause by the illegal hunted from society who lived on the habitat of the black crested itself such us Minahasa Regency, north Minahasa, south Minahasa, Bolaangmongondow regency, Tomohon, and Bitung city. Since 2012, the media was compitting to announce the issue of black crested extinction which is being the genuine species of north Sulawesi. Therefore, depart from the case, researcher was conducting the research toward the campaign which has been done by one of the society development sector its Selamatkan yaki programme in rescuing the crested since 2013 at Baputih bawah subdistrict, Ranowulu district, Bitung city. Researcher had pointed Batuputih bawah as the in doing the research because it is bordering on the habitat for Macaca nigra which called as Tangkoko jungle and plants-cultivation of Batuangus. Theory which had supported this research was Act-planned theory where the main factor that decide the act-form is the act itself. Hence, the RARE transformation theory was being the basic movement Â ofÂ the campaign which was applied by the Selamatkan Yaki. Further, Qualitative method being the methodology of research. It is because the method focused on the implementation based on societyâ€™s life. Hence, the resulth of the researh showed that the campaign in Batuputih bawah subdistrict had been taking a good respond by the society. The society already knew that black crested itself was an endemic and being the icon of the province. It shown by the result of the interview about the decreasing of Macaca nigra. Accourding to IUCN (Internasional union of concervation nature), society was not concern to the situation where they still hunt, sell or even consume them. Therefore, the obstacle of the implementation of this program was only the tradition of the society which is hard to change about hunt and consume the â€œYaki hitamâ€. kata kunci: kampanye, â€œyaki hitamâ€, save Macaca nigra